2019
DOI: 10.1016/j.jhin.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of whole-genome sequencing to understanding of the epidemiology and control of meticillin-resistant Staphylococcus aureus

Abstract: In recent years, approaches to tracking the spread of methicillin-resistant Staphylococcus aureus (MRSA) as part of outbreak management have used conventional DNA-based methods including pulsed field gel electrophoresis (PFGE) and spa typing. However, when a predominant clone is present, these methods may be insufficiently discriminatory. We conducted a literature search to highlight how whole genome sequencing (WGS) has revolutionised the investigation of outbreaks of MRSA, including intra-hospital spread and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 71 publications
(121 reference statements)
1
41
0
1
Order By: Relevance
“…Our results provided evidence that a strain that seemed related to a cluster by AFLP and MLVA was unrelated using WGS data with 162 allelic cgMLST and 435 wgSNP differences. cgMLST established itself as a reliable and user-friendly tool that can be used for prospective surveillance and comparison between laboratories and differentiate with a higher resolution between relatedness due to transmission events compared to conventional molecular techniques [27,[39][40][41]. In our study, cgMLST confirmed four different genetic lineages and two clusters.…”
Section: Discussionsupporting
confidence: 62%
“…Our results provided evidence that a strain that seemed related to a cluster by AFLP and MLVA was unrelated using WGS data with 162 allelic cgMLST and 435 wgSNP differences. cgMLST established itself as a reliable and user-friendly tool that can be used for prospective surveillance and comparison between laboratories and differentiate with a higher resolution between relatedness due to transmission events compared to conventional molecular techniques [27,[39][40][41]. In our study, cgMLST confirmed four different genetic lineages and two clusters.…”
Section: Discussionsupporting
confidence: 62%
“…The evolving dynamics of clones spread from the community and hospitals is only becoming clear with the implementation of WGS studies. WGS is also able to exclude cross-transmission when isolates are different (Humphreys and Coleman, 2019). However, the technique is costly and requires trained staff to analyze and interpret the results.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges now are to make WGS technology more amenable for routine use and to develop an evidence‐based consensus for sequence difference thresholds for isolates that have been deemed to be part of the same outbreak, including protracted outbreaks. Using such data in a timely way would provide increased sensitivity in detecting cross‐transmission events at an earlier stage, with the potential to prevent outbreaks, and have a positive impact on infection prevention and control (Humphreys & Coleman 2019). Recently, the taxonomy of Lactobacillaceae and Leuconostocaceae on the basis of WGS was evaluated, and Zheng et al .…”
Section: Molecular Typing Methodsmentioning
confidence: 99%